(untitled) (Research, Society and Development, 2020)
This study aimed to know the academic perception of the water crisis in the Distrito Federal, Brazil. For this, it was realized descript research with a qualitative and quantitative approach. A total of 167 university students participated in the questionnaire applied in the study. The interviews were carried out in the Distrito Federal region. The data were collected according to the answers. It was verified the 79% of the university students think that the water crisis in the Distrito Federal is related to the lack of investments in technology and infrastructure, as well as the lack of nature conservation represented by the deforestation of the Cerrado and irregular land use. Most of the interviewees (87%) believe that the university can contribute with important solutions to overcome the water crisis, and the interdisciplinary mechanisms of Environmental Education are the key to conscious consumption. The research highlights the need for more widespread information on impacts on water use in order to contribute to the description of water crisis scenarios made according to the variations in perceptions of those addressed.